The Influence of AI-Powered Payroll Management on Financial Planning in Organizations - Fida Oktafiani (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
Artificial Intelligence (AI) has revolutionized various aspects of financial management in organizations, including payroll systems. This study aims to analyze the impact of AI-powered payroll management on financial planning in organizations, employees' financial literacy, and workplace productivity, with PT Telkom Jabodetabek as the research object. A quasi-experimental method was used to compare an experimental group that adopted AI-powered payroll systems with a control group using traditional payroll methods. The pretest and posttest results indicated a 20% increase in financial literacy and a 13% rise in workplace productivity after implementing AI payroll systems. Qualitative analysis from interviews with financial managers and HRD confirmed that AI-powered payroll enhances transparency and accountability in salary management. However, challenges in implementation include low technology adoption among employees and concerns regarding personal data security. Therefore, organizations should integrate financial literacy programs and technology training to maximize the benefits of this system. Overall, this study highlights that AI-powered payroll has significant potential to improve operational efficiency, employees' financial well-being, and workplace productivity, but its success depends on the organization's readiness to manage this digital transformation.